1991
DOI: 10.1007/bf00290989
|View full text |Cite
|
Sign up to set email alerts
|

Mono-association of mice with non-cultivable, intestinal, segmented, filamentous bacteria

Abstract: A technique is described so that mice mono-associated with non-cultivable, segmented filamentous bacteria (SFB's) can be produced for the first time. As SFB donors, mice were used which had an intestinal microflora consisting of both SFB's and bacteria of the genus Clostridium. Recipients were germ-free mice. It was demonstrated that the intraileal inoculation method was more effective than the orogastric route. Therefore, intestinal homogenates of donor mice were treated with filtered ethanol, diluted and adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…A segmented filamentous bacterium (SFB), thought to belong to the Gram-positive Clostridia (51), colonizes the normal small intestine after weaning (52) and reaches very high densities in the ileum of adult animals. The SFB cannot be recovered from the intestine and cultured in vitro (53,54), but can be easily seen in the ileum of normal FVB/N mice using the Warthin-Starry silver stain. SFB adheres to ileal enterocytes located in the upper half of the villus (Fig.…”
Section: Loss Of Paneth Cells Does Not Have Any Appreciable Effect Onmentioning
confidence: 99%
“…A segmented filamentous bacterium (SFB), thought to belong to the Gram-positive Clostridia (51), colonizes the normal small intestine after weaning (52) and reaches very high densities in the ileum of adult animals. The SFB cannot be recovered from the intestine and cultured in vitro (53,54), but can be easily seen in the ileum of normal FVB/N mice using the Warthin-Starry silver stain. SFB adheres to ileal enterocytes located in the upper half of the villus (Fig.…”
Section: Loss Of Paneth Cells Does Not Have Any Appreciable Effect Onmentioning
confidence: 99%
“…This Gram-positive, segmented obligate anaerobe is spore forming and was recognized as a dominant gut microbe of mice by Savage et al (35,38). Klaasen et al (39) recently isolated SFB by treating fecal material with organic solvents to kill vegetative organisms and administering a series of ever-weaker inocula into germ-free mice. Snel et al (37) used 16S ribosomal RNA sequence analysis to position the SFB of several vertebrates within the cluster of clostridial species.…”
Section: Is There a Delay In The Development Of Neonatal Humoral Mucomentioning
confidence: 99%
“…This study was greatly facilitated by the use of a monoculture of these organisms in formerly germfree mice (12). A comparative 16s rRNA analysis revealed that there is a phylogenetic relationship between the SFB found in mice and the genus Clostridium.…”
mentioning
confidence: 99%